Normative Analysis of Traditional Medicine Industry Licensing Violations in Cases of Illegal Herbal Products based on Statutory Regulations - Septia Salmaa Qoonitah; Nunik Nurhayati (Proceeding International Conference Restructuring and Transforming Law, 2026)
The development of the traditional medicine industry in Indonesia has experienced significant growth in line with the increasing public interest in herbal products, which are perceived as more natural and safer; however, such growth has not always been accompanied by compliance with licensing regulations, as evidenced by the persistence of practices such as production without marketing authorization, the use of fictitious marketing authorization numbers, and the mixing of pharmaceutical chemical substances into traditional medicine products. This research employs a normative juridical legal research method with a statutory approach, analyzing relevant laws and regulations, legal doctrines, and scientific literature related to business licensing and the regulation of the traditional medicine industry. The novelty of this study lies in the analysis of the legal position of KBLI 21022 as the basis of legal standing for the traditional medicine industry within the risk-based business licensing system, as well as its relation to violations involving fictitious marketing authorization numbers and the mixing of pharmaceutical chemical substances. The results indicate that KBLI 21022 has a constitutive role in determining the operational legality of the traditional medicine industry, serving as the basis for identifying business activities, determining risk levels, and establishing obligations such as fulfilling the Business Identification Number, Standard Certificate, production permits, and Marketing Authorization Number; moreover, Law Number 17 of 2023 concerning Health stipulates that production without a Marketing Authorization Number, the use of fictitious authorization numbers, and the mixing of pharmaceutical chemical substances constitute serious violations subject to administrative and criminal sanctions, with BPOM playing a central role in supervision and enforcement to ensure public health protection. Conclusion: Thus, the regulatory framework emphasizes the importance of compliance with risk-based licensing under KBLI 21022 and reinforces strict legal consequences for violations as part of safeguarding public health and ensuring legal certainty in the traditional medicine industry.